Rationale and Design of RNAFH Study: Effect of Rosuvastatin (10 mg/d) on Nonalcoholic Fatty Liver in Metabolic Syndrome Patients without Overt Diabetes Evaluated by 1H-Magnetic Resonance Spectroscopy - Fan Ping; Xuan Wang; Jing Yang; Mei-cen Zhou; Wei Li; Ling-ling Xu; Yu-xiu Li (International Journal of Endocrinology)
Objective. The RNAFH study (effect of rosuvastatin on nonalcoholic fatty liver disease in metabolic syndrome patients without overt diabetes evaluated by 1H-MRS) is a prospective randomized, single-center, open-label trail designed to assess the effect of rosuvastatin on the intrahepatocellular lipid (IHCL) level of nonalcoholic fatty liver disease (NAFLD). Methods. 40 NAFLD patients meeting inclusion and exclusion criteria with metabolic syndrome (MS) but without overt diabetes mellitus will be included. Patients will be randomized to 52-week treatment with either rosuvastatin (10 mg/d) or blank control. The primary end point is IHCL evaluated by 1H-MRS, which was considered to be the most accurate noninvasive method for the evaluation of NAFLD. Secondary end points include homeostasis model assessment of insulin resistance (HOMA-IR) index on behalf of insulin resistance level and lipid parameters. Safety indicators will be monitored such as liver function, renal function, muscle stability, and glucose metabolism. The aims of the present study are noteworthy in respect that (1) IHCL is a quantitative indicator for evaluating the degree of fatty liver disease and 1H-MRS is a noninvasive technique to provide this specific index precisely, (2) meanwhile the HOMA-IR index and lipid parameters will be monitored, and (3) the safety of rosuvastatin treatment for 52 weeks will be evaluated including glucose metabolism, muscle stability, liver function, and renal function.